Effects of Compression Garments on Lower Limb Muscle Activation via Electromyography Analysis during Running - Wang, Ping (2016)
Sports compression garments are common-selected sportswear to improve athletic performance and reduce sports injury. Since they consist of elastic textile that exerts compression and pressure onto the muscle,muscle activation is of interest to sports compression garment manufactures who seek to enhance sports performance through gradient compression garment design.However,there are few scientific investigations to explore this effect of muscle activation to evaluate the performance of sports compression garments during sport activity. In this paper, a systemic experimental protocol was presented to improve the quality of evaluation test under a standardized running test. Then muscle activation with and without wearing sport compression garments to highlight the changes caused by compression garment was investigated. The electromyography(EMG) signal was collected and processed by the proposed method to represent the muscle activation combined with gait analysis of running. As a result,the average muscle activation of gait cycle for the major muscles such as rectus femoris(RF) and gastrocnemius medialis(GM) revealed that they needed to exert more muscle force without wearing garment at certain periods for mid-stand and pre-swing phase within gait cycle. These lower muscle activation levels prolonged activity duration,reduced fatigue,and presented low risk for sport injury.Such an evaluation study therefore would scientifically prove the effect of compression garment and provide information on muscle activation and the ergonomic efficacy of gradient compression garment design.